A process-based, stage-structured model of potato cyst nematode population dynamics: Effects of temperature and resistance. (7th August 2021) - Ewing, David A.; Blok, Vivian; Kettle, Helen
Highlights: PCN multiplication ratios are predicted to increase under climate warming. Two generations of PCN within a season appear possible given climate projections. Two generations would require a diapause period of at most a few weeks. Climate impacts on PCN dynamics are small in comparison to potato resistance effects. Breeding and growing G. pallida resistant potatoes should be a priority. Abstract: Potato cyst nematodes (PCN) are responsible for large losses in potato yields in many of the world's potato-growing regions. As soil temperatures increase due to climate change, there is potential for faster growth rates of PCN, allowing development of multiple generations in a growing season. We develop a process-based temperature-dependent model representing the life cycle of Globodera pallida, comprising juvenile, adult and cyst/diapause stages. To incorporate variability in the amount of time spent in each stage caused by genetic/environmental variation, the model is based on a mix of ordinary differential equations (ODEs) with sub-stages, and delay differential equations (DDEs). The effect of climate change is incorporated through the influence of soil temperature on the rate of development and survival in the hatching and juvenile stages. The level of the plant resistance to PCN is incorporated via the proportion of juveniles which become adults. After comparing the model with field data we run simulations to explore the effects of temperature and resistance on PCN populations. We find that with higher temperatures and longer growing seasons multiple generations of PCN can develop within a season, provided any required diapause period is short. Despite this, we show that growing resistant potatoes is a very effective control strategy and planting potatoes with even moderate levels of resistance can counter the effects of climate change.